2015
DOI: 10.3390/fib3030265
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Engineered Peptide-Glycosaminoglycan Microfibrous Hybrid Scaffolds for Potential Applications in Cartilage Tissue Regeneration

Abstract: Advances in tissue engineering have enabled the ability to design and fabricate biomaterials at the nanoscale that can actively mimic the natural cellular environment of host tissue. Of all tissues, cartilage remains difficult to regenerate due to its avascular nature. Herein we have developed two new hybrid polypeptide-glycosaminoglycan microfibrous scaffold constructs and compared their abilities to stimulate cell adhesion, proliferation, sulfated proteoglycan synthesis and soluble collagen synthesis when se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 119 publications
0
1
0
Order By: Relevance
“…In a separate study, Biedermannova and colleagues showed that tryptophan-cage mini proteins can also interact via hydrogen bonding and stacking interactions between proline and tryptophan [61]. It has also been reported that upon incorporation of collagen to FMOC-valyl cetyl amide assemblies, large fibrillar matrices are formed [62]. It is likely that similar interactions allow for the incorporation of collagen onto CGA-AMP template.…”
Section: Self-assembly Of Cga-amp and Preparation Of Scaffoldsmentioning
confidence: 99%
“…In a separate study, Biedermannova and colleagues showed that tryptophan-cage mini proteins can also interact via hydrogen bonding and stacking interactions between proline and tryptophan [61]. It has also been reported that upon incorporation of collagen to FMOC-valyl cetyl amide assemblies, large fibrillar matrices are formed [62]. It is likely that similar interactions allow for the incorporation of collagen onto CGA-AMP template.…”
Section: Self-assembly Of Cga-amp and Preparation Of Scaffoldsmentioning
confidence: 99%